Dynamics of Changes in the Intensity of Hard and Soft Components of Cosmic Rays in the Atmosphere - Taroyan, A. S.; Kokanyan, E. P.; Taroyan, Y. A.; Maмyan, А. М.
The dynamics of changes in the homogeneous intensity of the hard and soft components of cosmic radiation and the intensity of each of them separately, depending on the length of the atmospheric air layer are studied in the work.
Keywords: Physics